Career Adaptability and Work Engagement of Millennial Startup Employees - Haryani, Novia (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
This study aims to determine the level of career adaptability and work engagement and the effect of career adaptability on work engagement in millennial generation employees at a startup company. This type of research is ex post facto with a quantitative approach. The population of this study amounted to 34 employees who work at the startup company. This research is a population study; therefore, it uses the entire population of employees. The instrument uses a psychological scale of career adaptability and works engagement. The validity of the research scale uses content validity by expert judgment. The reliability of the research scale was estimated using Cronbach Alpha and composite reliability. The results of the descriptive analysis show that the level of career adaptability and work engagement of millennial generation employees at A startup company is relatively high. The results of multiple linear regression analysis show that: (1) career adaptability affects work engagement, (2) career adaptability concerns and curiosity dimensions affect work engagement, (3) career adaptability dimensions control and confidence have no effect on work engagement.